Advanced robotic technology is the future of surgery - MD, Raul Sebastian (2022)
Currently, we live in a new era of minimally invasive surgery. Operations are more like video games thantraditional open surgeries. The old-fashioned expression that “a good surgery requires a large incision”has been completely abandoned in countries where medical technology and research are well structured.Within the modern minimally invasive surgeries over the last 30 years, laparoscopic surgery is the mostwell established and recognized approach. However, with development of advanced technologiesand intense research, robotic surgery has emerged in the last decade as an attractive alternative tolaparoscopic surgery. DOI: https://doi.org/10.25176/RFMH.v17.n3.1067